Development Of S-Quinolin-2-Yl-Methyldithiocarbazate Functionalized Magnetic Nanoparticles As Magnetic Solid Phase Adsorbent For The Determination Of Heavy Metals In Water Samples - Rahman, Ahmad Jazmi Abdul (2020)
S-quinolin-2-yl-methyl-dithiocarbazate functionalized magnetic nanoparticle(MNP-SQ2MDTC) as adsorbent in magnetic solid phase extraction (MSPE) was developed for the determination of Cd2+ and Cu2+ in water samples. The surface of MNP was first coated with 3-(aminopropyl)triethoxysilane (APTES) as cross-linker and then SQ2MDTC was incorporated covalently to the coated MNP. The structural and surface characteristics were investigated using Fourier Transform infrared spectroscopy (FT-IR), X-ray powder diffraction (XRD) spectroscopy, vibrating-sample magnetometry (VSM), field emission scanning electron microscopy (FESEM), and Brunauer-Emmett-Teller (BET) analysis. Various experimental parameters affecting MSPE such as pH, mass of adsorbent, sample volume, sonication time and type of desorption eluent had been investigated in detail to improve the extraction efficiency. The method validation under optimal MSPE conditions revealed a good linearity in the calibration range of 0.1–5.0 μg mL-1, with coefficient of determination (R2) of 0.995 and 0.996 for Cd2+ and Cu2+, respectively. The limits of detection (LOD) of the developed method for Cd2+ and Cu2+ were found to be 0.054 and 0.040 μg mL-1, and limit of quantification (LOQ) were 0.180 and 0.134 μg mL-1, respectively. The proposed method has been successfully validated by applying MNP-SQ2MDTC adsorbent for the determination of the analytes in river water samples.